Lead (Pb) Exposure on Hemoglobin Levels and Decreasing Lung Function of Fuel Station Workers Banjarmasin - Taufiqurrahman, Muhamad; Ansori, Isa; Noor, Meitria Syahadatina; Haryati, Haryati; Assagaf, Ali; Isa, Mohamad (Universitas Airlangga, 2024)
Introdution:Exposure to airborne pollutants such as lead (Pb) can cause health problems. Fuel stations are one of the places with a high risk of Pb exposure sourced from fuel or motor vehicle exhaust emissions. This research aims to know the effect of Pb exposure on hemoglobin levels and lung function in fuel station workers. Methods: This study was observational, analytical, and cross-sectional on 40 fuel station workers in South Banjarmasin District. Urinary Pb measurement was carried out by spectrophotometry, then the relationship to peripheral blood hemoglobin (Hb) levels and lung function was analyzed based on FEV1 (%), FVC (%), and FEV1/FVC ratio with a simple linear regression test. The data met the classical assumptions of normality, heteroscedasticity, and with no autocorrelation. If abnormal distribution was found, data transformation was carried out. Results: Study obtained urinary Pb levels below the normal threshold of 0.0356±0.0074 ppm. Respectively, urinary Pb levels did not have a significant effect on Hb levels (mean±SD:14.39±1.41, adjusted R2:6.2%, p=0.067), FEV1 (94.15±6.93, 5.8%, p=0.074) and FVC (89.68±6.24, 0.5%, p=0.380). However, urinary Pb significantly correlated with decreasing the FEV1/FVC ratio (90.87±3.36, 10%, p=0.026) with the equation y=96.550159.454x even without any obstruction value. Conclusion: This study showed that urinary Pb levels were normal. An increase in urinary Pb levels has a significant effect on decreasing the FEV1/FVC ratio. Prevention to reduce the health impacts of Pb needs to be taken. More research on at-risk populations with longer years of service needs to be done